Preparation of 2,6-Dideoxy Sugars Through a Gold-Catalyzed Petasis-Ferrier-like Reaction. - Chen, Xizhao. (Tufts Archival Research Center, 2017)
2,6-Dideoxy-sugars are a major component of many bioactive natural products and antibiotics. However, the production of deoxy-sugars normally requires de novo synthesis from non-sugar precursors. This conventional approach requires multiple steps, which are both time-consuming and low-yielding. Meanwhile, most approaches are specific for a particular target, and a general approach that will permit the construction of libraries of deoxy-sugars does not exist. Therefore, in this study, a new methodology providing a general route to deoxy-sugars from cheap and readily available precursors based on gold-catalyzed Petasis-Ferrier-like rearrangement was developed. A homopropargyl orthoester substrate for the gold-catalyzed Petasis-Ferrier-like rearrangement was synthesized from commercially available methyl-D-lactate in 6 steps. The homopropargyl orthoester then underwent cyclization upon the treatment with a gold catalyst. The cyclization step generated diastereomerically pure product with a 24% yield. this study has demonstrated and established the feasibility of gold (I)-catalyzed cycloisomerization with a new class of substrate, homopropargyl orthoester. Additional discovery also revealed the versatility of this type of reaction as the presence or absence of an additional group in the α-position of the terminal alkyne led to two different products. For future work, reaction conditions need to be optimized for this type of new chemistry. The final product in this study then can be further modified into a number of 2,6-dideoxy-sugars. This approach will eventually permit the production of deoxy-sugar libraries in a short period of time.